2015
DOI: 10.1186/s13223-015-0093-x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profiles in nasal fluid of patients with seasonal or persistent allergic rhinitis

Abstract: BackgroundNew therapeutic approaches with biologic agents such as anti-cytokine antibodies are currently on trial for the treatment of asthma, rhinosinusitis or allergic diseases necessitating patient selection by biomarkers. Allergic rhinitis (AR), affecting about 20 % of the Canadian population, is an inflammatory disease characterised by a disequilibrium of T-lymphocytes and tissue eosinophilia. Aim of the present study was to describe distinct cytokine patterns in nasal secretion between seasonal and peren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 41 publications
5
35
1
5
Order By: Relevance
“…Allergic rhinitis is the inflammation of the nasal membranes that is characterized by sneezing, nasal congestion, nasal itching, and rhinorrhea in any combination (1). Studies performed in Western Europe have shown that allergic rhinitis has a high prevalence and is frequently undiagnosed (2, 3).…”
Section: Introductionmentioning
confidence: 99%
“…Allergic rhinitis is the inflammation of the nasal membranes that is characterized by sneezing, nasal congestion, nasal itching, and rhinorrhea in any combination (1). Studies performed in Western Europe have shown that allergic rhinitis has a high prevalence and is frequently undiagnosed (2, 3).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, AR is characterized by a Th2-driven inflammation with prevalent eosinophilic infiltrate [3]. Also, allergic asthma is characterized by mucosal eosinophilic inflammation, bronchial hyperresponsiveness (BHR) to different stimuli, and variable and reversible bronchial obstruction [4].…”
Section: Introductionmentioning
confidence: 99%
“…Benson et al (21) found that IL-10 level in nasal fluid is increased patients with AR compared to the control group during pollen season and reduced by corticosteroid therapy. In another study, IL-10 was found to be significantly decreased in AR patients compared to the control group (24). According to our data, IL-10 level was increased in AR group and it significantly decreased after PYC treatment at doses both 3 mg/ kg and 10 mg/kg.…”
Section: Groupsmentioning
confidence: 54%